Bangladesh: A Scientometric Analysis of National Publications Output in S&T, 2001-10 - Gupta, B.M. (DESIDOC Journal of Library & Information Technology, 2013)
This study analyses the research output of Bangladesh in S&T during 2001-10 on several parametersincluding its growth and country publications share in the world’s research output, country publicationsshare in various subjects in the national and global context, pattern of research communication in coredomestic and international journals, geographical distribution of publications, share of internationalcollaborative publications at the national-level as well as across subjects and characteristics of highproductivity institutions, authors, and cited papers. The Scopus Citation database has been used toretrieve the publication data for 10 years. It concludes that Bangladesh needs to increase its output and bring about improvement in the quality of its research efforts further. http://dx.doi.org/10.14429/djlit.33.1.3728